The female athlete triad and relative energy deficiency in sport: Knowledge of both can improve the health of female athletes. - Valliant, M. W. (Strength and Conditioning Journal, 2016)
Female athletes are at risk of consuming inadequate energy for a variety of reasons. Two syndromes, the female athlete triad and relative energy deficiency in sport, have been proposed. There is partial overlap in the components that make up the syndrome; the underlying issue with both is regarding energy availability. Thus, it is critical to ensure that athletes are aware of their energy needs and energy intake. Regular health screening and preventive measures are best practice in maintaining the health of an athlete, as is ensuring that all athletic staff receives regular education on these topics.